Review Literatur Pengaruh Pendidikan Kesehatan terhadap Pengetahuan dan Sikap Remaja tentang HIV/AIDS - Nina Salsabilla; Reyna Agesti (MEJORA Medical Journal Awatara, 2025)
Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) remain significant global public health problems, particularly among adolescents who are vulnerable due to psychosocial and behavioral factors. This study aims to review the influence of health education on adolescents’ knowledge and attitudes toward HIV/AIDS and to identify factors affecting prevention efforts. This research employed a literature review approach by analyzing scientific articles published between 2017 and 2025 obtained from Google Scholar, ProQuest, and Semantic Scholar. Articles were selected based on relevance to adolescent populations, HIV/AIDS knowledge, attitudes, stigma, and health education interventions. The findings indicate that health education consistently improves adolescents’ knowledge and fosters more positive attitudes toward HIV/AIDS prevention. Adequate knowledge is associated with reduced stigma and safer behaviors. Individual characteristics such as age, education level, gender, and sources of information, as well as environmental and social support factors, significantly influence knowledge and attitudes. Peer education, interpersonal communication, and adolescent empowerment programs are shown to be effective strategies. In conclusion, health education plays a vital role in HIV/AIDS prevention among adolescents. Effective programs should be tailored to demographic and social contexts, emphasize participatory approaches, and integrate peer support to promote sustainable behavioral change.